Population genetic structure and connectivity of the seagrass Thalassia hemprichii in the Western Indian Ocean is influenced by predominant ocean currents - Marlene Jahnke; Martin Gullström; Josefine Larsson; Maria E. Asplund; Said Mgeleka; Mathew Ogalo Silas; Arielle Hoamby; Jamal Mahafina; Lina Mtwana Nordlund (Ecology and Evolution, 2019)
Abstract This study is the first large‐scale genetic population study of a widespread climax species of seagrass, Thalassia hemprichii, in the Western Indian Ocean (WIO). The aim was to understand genetic population structure and connectivity of T. hemprichii in relation to hydrodynamic features. We genotyped 205 individual seagrass shoots from 11 sites across the WIO, spanning over a distance of ~2,700 km, with twelve microsatellite markers. Seagrass shoots were sampled in Kenya, Tanzania (mainland and Zanzibar), Mozambique, and Madagascar: 4–26°S and 33–48°E. We assessed clonality and visualized genetic diversity and genetic population differentiation. We used Bayesian clustering approaches (TESS) to trace spatial ancestry of populations and used directional migration rates (DivMigrate) to identify sources of gene flow. We identified four genetically differentiated groups: (a) samples from the Zanzibar channel; (b) Mozambique; (c) Madagascar; and (d) the east coast of Zanzibar and Kenya. Significant pairwise population genetic differentiation was found among many sites. Isolation by distance was detected for the estimated magnitude of divergence (DEST), but the three predominant ocean current systems (i.e., East African Coastal Current, North East Madagascar Current, and the South Equatorial Current) also determine genetic connectivity and genetic structure. Directional migration rates indicate that Madagascar acts as an important source population. Overall, clonality was moderate to high with large differences among sampling sites, indicating relatively low, but spatially variable sexual reproduction rates. The strongest genetic break was identified for three sites in the Zanzibar channel. Although isolation by distance is present, this study suggests that the three regionally predominant ocean current systems (i.e., East African Coastal Current, North East Madagascar Current, and the South Equatorial Current) rather than distance determine genetic connectivity and structure of T. hemprichii in the WIO. If the goal is to maintain genetic connectivity of T. hemprichii within the WIO, conservation planning and implementation of marine protection should be considered at the regional scale—across national borders.